Physisorption of ammonia on AISI 304 L stainless steel at different surface temperature under high vacuum conditions. (December 2016) - de Castro, A.; Alegre, D.; Tabarés, F.L.
Highlights: Quantification of the ammonia physisorption on AISI 304 L steel at different surface temperatures (323-473 K) has been carried out by means of mass spectrometry. Ammonia retention is in the range of µg/cm 2 . Lower retentions are obtained for higher surface temperatures except at 323 and 373 K. The sticking coefficient fit allows the estimation of the activation energy of the multilayer adsorption (0.15 eV per molecule). The normalization of the characteristic decay time for the physisorption (τ) could give an approximation for the ammonia sticking in ITER vacuum lines with higher particle fluxes. Abstract: The physisorption of ammonia molecules (sticking) on the walls of a stainless steel pipe (AISI 304 L) has been studied at different wall temperatures (323-473 K). The total amount of ammonia that is retained on the walls, once equilibrium is reached, has been measured by differentially-pumped mass spectrometry in gas exposure laboratory experiments. The results show ammonia retentions in the range of μg/cm 2 resulting in a multilayer adsorption with lower amounts of stuck ammonia at higher temperatures of the stainless steel surface. The sticking coefficient follows an exponential decay evolution with time. The activation energy of the process has been estimated by an Arrhenius fit, assuming that the characteristic time for this decay is inversely proportional to the kinetic adsorption constant. A value of 0.15 eV per ammonia molecule has been obtained, being in agreement with nominal values for the physisorption of small molecules or atoms (CO, N2, Ar…) that can be found in the specialized literature. The implication of these results in the possible extrapolation to the ITER vacuum system under nitrogen seeded plasma operation is also addressed.